Bridging or Bypassing: Generational Differences in Trust and Source Credibility in Media Ecosystems - Harliantara; Bahar Öztürk (UPT Publikasi Ilmiah UNISBA, 2026)
This study examines how Generations Z, Millennials, and X perceive source credibility within an integrated media ecosystem, where traditional and digital platforms converge amid collapsing institutional trust. While the existing literature addresses the crisis of trust in institutionalized media, little research has examined how generational cognitive preferences translate into specific behaviors within actual integrated settings, specifically the mechanisms of bridging or bypassing information sources. The findings reveal distinct patterns: Gen X predominantly bypasses digital sources due to heavy reliance on institutions, and Millennials systematically cross-validate to build “bridges.” In contrast, Gen Z, driven by networked authenticity, bypasses traditional outlets. These findings are crucial for media literacy and legacy media adaptation in the age of audience fragmentation. This study proposes a hybrid communication framework for media organizations to regain relevance across diverse age groups.